LONG-TERM RESULTS OF SURGICAL TREATMENT FOR PANCREATIC CANCER. A REVIEW OF THE LITERATURE - B. N. GURMIKOV; M. S. BOLOKOV; N. L. GURMIKOVA (Кубанский научный медицинский вестник)
In recent decades, there is a trend towards growth and relatively high incidence of pancreatic cancer. Long-term results of surgical treatment remain unsatisfactory. However, in view of the progress of medical technology and the development of new surgical approaches to the treatment of pancreatic cancer, interest is the current state of the problem. This literature review focuses on the long-term outcomes of surgical treatment in patients with pancreatic cancer.